2015
DOI: 10.1038/ncomms9567
|View full text |Cite
|
Sign up to set email alerts
|

The deuterium/hydrogen distribution in chondritic organic matter attests to early ionizing irradiation

Abstract: Primitive carbonaceous chondrites contain a large array of organic compounds dominated by insoluble organic matter (IOM). A striking feature of this IOM is the systematic enrichment in deuterium compared with the solar hydrogen reservoir. This enrichment has been taken as a sign of low-temperature ion-molecule or gas-grain reactions. However, the extent to which Solar System processes, especially ionizing radiation, can affect D/H ratios is largely unknown. Here, we report the effects of electron irradiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
(42 reference statements)
3
28
1
Order By: Relevance
“…; Laurent et al. , ). Alternatively, they may have originated from different soluble precursors that led to different IOM signatures upon hydrothermal processing.…”
Section: Discussionmentioning
confidence: 97%
“…; Laurent et al. , ). Alternatively, they may have originated from different soluble precursors that led to different IOM signatures upon hydrothermal processing.…”
Section: Discussionmentioning
confidence: 97%
“…; Laurent et al. ). It was also suggested that the oxidation of iron by water on the parent body may have induced large D‐enrichment in organic matter (Alexander et al.…”
Section: Resultsmentioning
confidence: 98%
“…), the protosolar nebula (Willacy and Woods ; Laurent et al. ), and in the parent body (Eiler and Kitchen ). Among different possible processes, the effects of electron irradiation in the solar nebula have been proposed recently to account for large D‐enrichments in organic matter (Le Guillou et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations